Pengaruh Pemberian Media Kartu Suku Kata Terhadap Kemampuan Kualitas Membaca pada Siswa - Tanjung, Cici Febi Putri; Anas, Nirwana (LP. Ma'arif Janggan Magetan, 2023)
Syllable card media is a tool aimed at enhancing students' early reading skills by visualizing images and syllables that are affixed to a board. The purpose of this study is to investigate the Influence of Syllable Card Media on Reading Ability Quality of Students. The research was conducted at a public elementary school in Deli Serdang, with the subjects being second semester first-grade students, consisting of two classes: class IA and 1B. The research utilized a quantitative method with a Quasi-Experimental approach. The results from the Wilcoxon signed-rank test indicated an Asymp. Sig (2-tailed) value of 0.000, which is smaller than 0.05 (0.000 < 0.05). This leads to the conclusion that the